MOF‐Based Mixed‐Matrix Membranes in Gas Separation – Mystery and Reality1. Issue 11 (27th July 2016) - Friebe, Sebastian; Diestel, Lisa; Knebel, Alexander; Wollbrink, Alexander; Caro, Jürgen
Abstract: Microporous additives like nanosized metal‐organic framework (MOF) particles can improve the gas separation performance of polymer membranes. These membranes which consist of added filler particles in a continuous polymer phase are called mixed‐matrix membranes (MMM). While inorganic zeolites and organic polymers do not match well, the preparation of defect‐free MOF‐based MMMs is much easier. However, some problems can also occur during the preparation. Solutions how to avoid them and prepare perfect MMMs are given. In practical gas separation, the selectivity of the MMMs was found to be even higher than predicted by the Maxwell model. Abstract : In mixed‐matrix membranes (MMMs), suitable microporous nanosized filler like zeolite or carbon can modify the permeation properties of a polymer. Metal‐organic frameworks (MOFs) are very promising filler materials for MMMs. The chemistry of MOFs allows for covalent linkage to the polymer. MOFs can be prepared as nanoparticles and as delaminated two‐dimensional nanosheets.